Changes in mechanical properties and fracture behaviors of heated marble subjected to liquid nitrogen cooling. (15th February 2022) - Su, Shanjie; Hou, Peng; Gao, Feng; Liang, Xin; Ding, Ruoyao; Cai, Chengzheng
Abstract: Liquid nitrogen (LN2 ) fracturing is a novel waterless fracturing technology that has significant potential for application in the development of geothermal resources. In this study, we performed physical and mechanical experiments on marble samples to determine the influence of LN2 cooling on the damage behavior of hot dry rock (HDR). Specifically, we evaluated the changes in the internal structure, mechanical properties, and fracture behavior of the marble samples after subjecting them to thermal shock. The results revealed that the porosity of the heated marble increased significantly after LN2 cooling, whereas the P-wave velocity, compression strength, and elastic modulus decreased. The complexity of the fracture propagation process and the induced fracture morphology of the marble samples subjected to thermal shock increased under uniaxial compression. Furthermore, the changes in these properties increased with the increase in the marble temperature. Compared to air cooling, LN2 cooling significantly changes the physical and mechanical properties and fracture behavior of marble. Based on the coupled thermal–mechanical simulations from macroscopic and microscopic perspectives, the thermal damage that occurs in heated marble subjected to rapid cooling is primarily due to the temperature gradient inside the rock and the difference in the thermal expansion of adjacent mineral particles.